2011
DOI: 10.1136/bmj.d8012
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitors during pregnancy and risk of persistent pulmonary hypertension in the newborn: population based cohort study from the five Nordic countries

Abstract: Objective To assess whether maternal use of selective serotonin reuptake inhibitors (SSRIs) increases the risk of persistent pulmonary hypertension in the newborn, and whether such an effect might differ between specific SSRIs.Design Population based cohort study using data from the national health registers.Setting Denmark, Finland, Iceland, Norway, and Sweden, 1996-2007. Participants More than 1.6 million infants born after gestational week 33.Main outcome measures Risks of persistent pulmonary hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
182
2
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(199 citation statements)
references
References 31 publications
9
182
2
6
Order By: Relevance
“…14 Although some meta-analyses have provided risk estimates that have not been confirmed at the same magnitude in some other studies, we do know that SSRI use may be related, for example, to pulmonary hypertension; although the risk of persistent pulmonary hypertension of the newborn is low, use of SSRIs in late pregnancy increases that risk more than twofold. 15 One meta-analysis found that paroxetine and fluoxetine are associated with a small, but significantly increased risk of major malformations and paroxetine in particular is associated with cardiac malformation. 14 While a systematic review did not show increased risk of heart defects or minor malformations, it did detect an increased risk of major malformations and miscarriage following the use of SSRIs during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…14 Although some meta-analyses have provided risk estimates that have not been confirmed at the same magnitude in some other studies, we do know that SSRI use may be related, for example, to pulmonary hypertension; although the risk of persistent pulmonary hypertension of the newborn is low, use of SSRIs in late pregnancy increases that risk more than twofold. 15 One meta-analysis found that paroxetine and fluoxetine are associated with a small, but significantly increased risk of major malformations and paroxetine in particular is associated with cardiac malformation. 14 While a systematic review did not show increased risk of heart defects or minor malformations, it did detect an increased risk of major malformations and miscarriage following the use of SSRIs during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Infants exposed to SSRIs in the final trimester should be considered at risk of adaptation symptoms and should be monitored accordingly. The critical condition of persistent pulmonary hypertension is reported across a number of large cohorts to be increased across SSRIs, with Kieler et al 55 suggesting that there is a class effect. Later exposure is reported to carry the increased risk.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…SSRIs Six studies investigated the prevalence of persistent pulmonary hypertension following prenatal exposure to SSRIs [52][53][54][55][56][57] and four demonstrated an association [53][54][55][56] ( 55 demonstrated that the risk of persistent pulmonary hypertension was similar across all SSRIs studied (sertraline, citalopram, paroxetine, and fluoxetine) and concluded that this indicated a treatment class effect. No other identified studies investigated the prevalence of persistent pulmonary hypertension following exposure to specific SSRI treatment types.…”
Section: Persistent Pulmonary Hypertensionmentioning
confidence: 99%
“…[10][11][12][13]37,38 One recent study of the association between selective serotonin reuptake inhibitors and PPHN risk from 5 Nordic countries observed no association between NSAID use and PPHN. 39 The main limitation of the current study is the reliance on maternal recall for information about exposure status. Several factors suggest, however, that recall bias is an unlikely explanation for our study results.…”
Section: Figurementioning
confidence: 99%